Contemporary groundwater pollution studies in India - Banerjee, D.; Mukherjee, Abhijit; Acharyya, S.; Chatterjee, D.; Mahanta, C.; Saha, D.; Kumar, S.; Singh, M.; Sarkar, A.; Sengupta, S.; Dubey, C.; Shukla, D.; et al. (2012)
This review contains a summary of the work done on arsenic and flouride pollution of the surface and groundwater in parts of the Indian peninsula and Ganga-Brahmaputra Alluvial and Delta Plains. Results of the investigation have been be categorized institutions wise with identification of the principal worker in the research group. © Printed in India.